Where have all the youngest gone? The postlarval and young stages of the Mediterranean endangered limpet Patella ferruginea Gmelin, 1791 - GUALLART, J.; PEÑA, J. B.; LUQUE, Á. A.; TEMPLADO, J. (Mediterranean Marine Science, 2018)
Recruits of Patella ferruginea are hardly seen in their habitat, hence the precise level where they settle and the morphology of the earliest growth stages remain unknown. The earliest postlarval stages of this species are here described for the first time, based on specimens both obtained through controlled reproduction and observed in its natural environment in Chafarinas Islands (North Africa). Young postlarval specimens of 290 μm in length settled slightly below the water level on aquaculture tank floating Petri dishes. Specimens of about 4 mm were found in its natural habitat at the level of the vermetid gastropod Dendropoma lebeche, whereas those larger than 8 mm were found at this level, but also in the upper midlittoral, at the Chthamalus spp. fringe. The characteristic starlike shell and colour pattern with alternating concentric dark and light bands of young specimens appeared at about 8 mm. Smaller specimens have a more or less oval shell and dark radial bands. This information is useful for future non-invasive studies on the recruitment of this endangered species, but further information about the postlarval stages of the other three Mediterranean patellid species is needed to distinguish specimens smaller than 3 mm.